Climate change mitigation in forests: Conflict, peacebuilding, and lessons for climate security - Position Paper - Myers, Rodd; Luttrell, Cecilia; Harjanthi, Rahayu; Fisher, Micah R.; Menton, Mary; Läderach, Peter R.D.; Wollenberg, Eva Karoline (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate change mitigation in forests: Conflict, peacebuilding, and lessons for climate security III There is growing awareness of the link between climate change and security. Most of the climate security debate has focused on the ways that climate change exacerbates geopolitical and state security matters through ‘threat multipliers’, especially in terms of intra-state, inter-group and sub-national conflicts. At the same time, 64 per cent of climate finance was allocated to mitigation and 25 per cent to adaptation between 2013 and 2019 (OECD 2020; OECD 2021). Despite this, the dynamics between climate change mitigation and security remains a less-explored topic. As climate security attracts increasing attention in research and policy, our entry point into reviewing the links between climate change mitigation and security is rooted in studies of conflict and peace in environmental governance. Because forests are a global focus of climate change mitigation, we focus our review on initiatives that directly affect, or are implemented in, forest areas in low- and middle-income countries. Forests have complex governance contexts and are prone to conflict due to histories of colonization and ongoing resource extraction that lead to disputes over who has authority to make decisions, how different actors are compensated, and whose priorities and claims dictate actions in forest areas. CCMIs related to forests are often inserted into these long-standing conflicts. Many of these tensions over rights and resources are located in fragile states and some in armed conflict and post-conflict contexts. Conflict and weak institutional governance are often associated with deforestation but have also been shown to protect forest resources when insurgent forces are compelled to do so.